Pharmacological characterisation of arthritis induced by Bothrops jararaca venom in rabbits: a positive cross talk between bradykinin, nitric oxide and prostaglandin E2 - Suzana B. V. Mello; Maria Luiza Guzzo; Luiz Filipe Santiago Lisboa; Sandra H. P. Farsky (Mediators of Inflammation)
Background: Our previous results showed that nitric oxide (NO) and bradykinin (BK) mediate the arthritis induced by Bothrops jararaca venom (BjV) in rabbits. In this study, we investigated the contribution of each receptor of BK as well as the inter-relationship between NO and eicosanoids in BjV-induced arthritis.